Enhancing Thai Students' Speaking Skills Through Debate: A Case Study At Darul Ulum School, Satun, Thailand - Kurnia, Soechi; Syahputra, Bambang Panca; Hum, M. (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the effectiveness of using debate as a method to enhance Thai students’ English-speaking skills at Darul Ulum School, Satun, Thailand. The research was conducted using a Classroom Action Research (CAR) design, which focused on the integration of debate activities into the learning process to improve students’ speaking proficiency. The participants of this study consisted of 30 students from Class X at Darul Ulum School. The data were analyzed using the paired sample t-test to assess the improvement in students' speaking performance before and after the intervention. The results showed a significant increase in students’ English-speaking skills, with a p-value less than 0.000 and a t-count of 6.901, which is greater than the t-table value of 1.669. These findings indicate that the use of debate significantly enhances students’ speaking abilities. Debate encourages real-time thinking, promotes critical analysis, and helps students articulate their thoughts more clearly and confidently, making it an effective strategy for improving English-speaking skills in the classroom.